The Canadian Broadcasting Corporation and the Making of Literary Audiences in Digital Spaces - Martínez-Zalce, Graciela (Association française des études canadiennes (AFEC), 2023)
In the 21st century, can a mandate like the Canadian Broadcasting Corporation’s stay operational? How has the corporation’s nationalist position had to change in order to continue to represent modern Canadian society? How did the CBC adapt to new ways of communicating through social media? This article will analyze how the Canadian Broadcasting Corporation (CBC) has responded to contemporary ways of sharing content on social media to disseminate national literatures in various ways, using at least three outlets (CBC’s Canada Reads, and Canada Writes) which bring together a community of practice whose members share content on several stages of the craft of writing and the skills required to publish. Using the small-stories method (GEORGAKOUPOULOU), this article will analyze narrative activities that are important to recognizing the identity-forging work of storytellers, either as Canadian readers or as Canadian writers, as well as the social fabric of practices that people become involved in, with the objective of discovering how the CBC has created a virtual community of practice (as conceived by Robert V. Kozinets), how it has successfully furthered the goal of discussing Canadian identities in this century, and whether and how it has raised awareness around non-mainstream authors.